Perspectives and use of telemedicine by doctors in India: a cross-sectional study - Nagaraja, Vikranth H.; Ghosh Dastidar, Biswanath; Suri, Shailesh; Jani, Anant (Health policy and technology, 2024)
Background - India has committed to formulating a roadmap for realising a resilient health system, with digital health being an important element. Following the successful implementation of a free telemedicine service, eSanjeevani, India published the Telemedicine Practice Guidelines in 2020 to scale telemedicine use in India. The current study aims to understand the perspective and use of telemedicine by medical doctors in India after the release of these guidelines. - Methods - Data were acquired through an anonymous, cross-sectional, internet-based survey of medical doctors (n = 444) at a pan-India level. Replies were subjected to statistical analysis. - Findings - Telemedicine was used for various non-mutually exclusive reasons, with the top two reasons being live audio or video consultations (60.4 %) and online payments (19.1 %), and smartphones were the most frequently used device type (60.6 %). Among various benefits of telemedicine, almost all respondents (93 %) recognised the potential for telemedicine to reduce COVID-19 infection risk for healthcare professionals. Interestingly, nearly 45 % of respondents felt that limited and fragmented insurance coverage was an important limitation to the practice of telemedicine in India, and 49 % believed reduced patient fees for teleconsultations could help incentivise telemedicine use. - Interpretation - This study helps to appraise the use of telemedicine in India after the publication of telemedicine guidelines in 2020. Furthermore, the findings can inform the development of telemedicine platforms, policies and incentives to improve the design and implementation of effective telemedicine in India. - Funding - No funding to report.